International experiences inhe tourism place meaking for eco-tourism purposes (Journal of Planner and Development, 2023)
The research paper deals with the role of the place making in eco-tourism through a review of international experiences in the eco-tourism industry and its contribution to advancing the reality of tourism there, and attracting the largest number of tourists. The study is divided into five axes: the first is a study of related concepts, and the second is a study of global experiences, which included three countries: (South Bank (Gabriel’s Wharf) - London, Rotterdam in the Netherlands, and dealt with each of Happy Streets and Kendrick Mills, and then the Perak River tourist corridor - Malaysia). As for the third axis, it is concerned with analyzing these experiences to reach the fourth axis, which is related to the practical framework and the field study of the city of Hit and the most important ingredients and capabilities it possesses for environmental tourism attraction, and then analyzing the region to know the types of ecotourism available and that may be available in it, as well as the capabilities and determinants that hinder its availability, as well as Clarifying the types of place making that can be applied in the city of Heat and clarifying some examples of them to advance the environmental tourism situation in it, using the method of making the tourist place. Finally, the fifth axis is related to the conclusions and recommendations that can be taken toadvance the environmental tourism reality of tourist destinations. Place Making Ecotourism Gabriel Wharf Rotterdam Heet Perak River Heet Waterwheels.